Ideology and gender in political literature: a feminist reading of Indonesian political dramas - Muhammad Rasyid Ridlo (Indonesian Journal of Politics and Literary Studies, 2026)
Background: Indonesian political drama serves as a medium of resistance but often embeds patriarchal views of gender and agency. Objective: This study examines how political ideology and gender intersect in dramas by W.S. Rendra and Nano Riantiarno. Method: A qualitative approach integrates Feminist Critical Discourse Analysis, narrative, and ideological analysis. Results: Male characters dominate political discourse, while women are positioned as moral or subordinate figures; narratively, they function as catalysts or victims, and symbolically as markers of patriarchal power. Implication: These findings reveal that political drama both critiques authoritarianism and reproduces gender inequality, calling for feminist reinterpretation. Novelty: This study offers an integrative framework linking discourse, narrative, and stage symbolism to expose gendered power within political theatre.